Factors influencing the SARS-CoV-2 infection and vaccination induced immune response in rheumatoid arthritis - Nemeth, Dora; Vago, Hajnalka; Tothfalusi, Laszlo; Ulakcsai, Zsuzsanna; Becker, David; Szabo, Zsofia; Rojkovich, Bernadett; Merkely, Bela; Nagy, Gyorgy (Frontiers in Immunology, 2022)
Background To investigate the factors that have significant impact on the Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) infection and vaccination induced immune response in rheumatoid arthritis (RA). Methods Serological response was measured by quantifying anti-SARS-CoV-2 specific antibodies, while the cell-mediated response was measured by a whole-blood test quantifying the interferon (IFN)-γ response to different SARS-CoV-2-specific domains. Results We prospectively enrolled 109 RA patients and 43 healthy controls. The median time (IQR) between the confirmed infection or the last vaccination dose and the day when samples were taken (“sampling interval”) was 3.67 (2.03, 5.50) months in the RA group. Anti-Spike (anti-S) specific antibodies were detected in 94% of RA patients. Among the investigated patient related variables, age (p<0.004), sampling interval (p<0.001), the brand of the vaccine (p<0.001) and targeted RA therapy (TNF-inhibitor, IL-6 inhibitor, anti-CD20 therapy) had significant effect on the anti-S levels. After covariate adjustment TNF-inhibitor therapy decreased the anti-S antibody concentrations by 80% (p<0.001). The same figures for IL-6 inhibitor and anti-CD20 therapy were 74% (p=0.049) and 97% (p=0.002), respectively. Compared to subjects who were infected but were not vaccinated, the RNA COVID-19 vaccines increased the anti-S antibody levels to 71.1 (mRNA-1273) and 36.0 (BNT162b2) fold (p<0.001). The corresponding figure for the ChAdOx1s vaccine is 18.1(p=0.037). Anti-CCP (anti-cyclic citrullinated peptides) positive patients had 6.28 times (p= 0.00165) higher anti-S levels, than the anti-CCP negative patients. Positive T-cell response was observed in 87% of the healthy volunteer group and in 52% of the RA patient group. Following vaccination or infection it declined significantly (p= 0.044) but more slowly than that of anti-S titer (6%/month versus 25%). Specific T-cell responses were decreased by 65% in patients treated with anti-CD20 therapy (p=0.055). Conclusion Our study showed that the SARS-CoV-2-specific antibody levels were substantially reduced in RA patients treated with TNF-α-inhibitors (N=51) and IL-6-inhibitor (N=15). In addition, anti-CD20 therapy (N=4) inhibited both SARS-CoV-2-induced humoral and cellular immune responses. Furthermore, the magnitude of humoral and cellular immune response was dependent on the age and decreased over time. The RNA vaccines and ChAdOx1s vaccine effectively increased the level of anti-S antibodies.